2002
DOI: 10.1111/j.1095-8649.2002.tb02428.x
|View full text |Cite
|
Sign up to set email alerts
|

Isozyme variation among four species of the catfish genus Clarias

Abstract: Native Thai species of Clarias catfishes and one species introduced from Africa can be easily distinguished by horizontal starch gel electrophoresis of allozymes. An undescribed species of Clarias was collected from Thailand and found to possess several fixed allelic differences from the Clarias previously studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Therefore, correct species labeling, morphological taxonomy and voucher documentation should be prioritized in case that reassessment of spurious data is necessary [23] . Mislabeling is not unexpected since both of these species are genetically homologous [24] and morphologically similar. It has been reported that C. macrocephalus could not be distinguished from a female C. batrachus [25] .…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, correct species labeling, morphological taxonomy and voucher documentation should be prioritized in case that reassessment of spurious data is necessary [23] . Mislabeling is not unexpected since both of these species are genetically homologous [24] and morphologically similar. It has been reported that C. macrocephalus could not be distinguished from a female C. batrachus [25] .…”
Section: Discussionmentioning
confidence: 91%
“…AAAAAA 1 Genetic distance Nei's (1978) Genetic distance Nei's (1978) Nei's (1978) unbiased genetic distance based on mtDNA RFLP analysis of three Clarias species. Genetic distance/bootstrap value of each node indicated Agnese et al, 1997;Na-Nakorn et al, 1998, 2002. The observed heterozygosity values were comparable in samples of C. gariepinus from both India and Thailand (0.149 and 0.152, respectively), but higher than that observed for C. batrachus (0.05) and C. macrocephalus (0.08).…”
Section: Discussionmentioning
confidence: 69%
“…As against the values in the present study, the P and H for other African catfishes were: in Chrysichtys auratus (Geoffroy Saint-Hilaire) P varied from 0% to 10% and H ¼ 0.000-0.081 (Agnese, 1991); in Chrysichtys nigrodigitatus P ¼ 5-21% and H ¼ 0.017-0.080 (Agnese et al, 1989). Na-Nakorn et al (2002) estimated 15.4% polymorphic loci in C. gariepinus from Thailand with the observed heterozygosity (Hobs ¼ 0.055) and mean no. of alleles to be 1.2.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…They found that a combined approach using three assays could reliably distinguish these two species in this case. Na-Nakorn et al (2002) found that isozyme markers could be used to make clear distinctions among four Clarias species found in Thailand.…”
Section: Molecular Markers For Species Identification and Analysis Of...mentioning
confidence: 99%